Pemberian Literasi Asuransi Kepada Mahasiswa : InsurTech - Revolusi Perkembangan, Mekanisme dan Peluang Karir di Era Digital - Alvernia Kurniartha; Wahyuari Wahyuari (Universitas Negeri Jakarta, 2026)
The insurance industry plays an important role in supporting national economic stability and growth, including supporting the banking sector through investment synergies, risk management, and product cooperation. However, public understanding of the insurance industry is still low compared to the banking sector. Data from the 2025 National Financial Literacy and Inclusion Survey (SNLIK) conducted by the OJK and BPS shows the insurance literacy index is 45.45% and insurance inclusion index is 28.50%. There is a gap, with the insurance literacy index 16.95% higher than the insurance inclusion index. However, the insurance literacy index remains below 50%. Therefore, regulators (OJK), insurance industry players, insurance associations, and Civitas Academica need to continue efforts to provide insurance literacy to the public to increase the insurance inclusion index. Furthermore, developing innovations, such as adopting and optimizing the use of technology in insurance operations and marketing, can also trigger the increasing of insurance inclusion in this digital era. Technological advances have created many new breakthroughs in the insurance business, named as Insurance Technology (Insurtech). Along with the development of Insurtech, new kind of jobs are emerging that require future human resources of digital insurance. For this reasons, lecturers at Sekolah Tinggi Manajemen Asuransi (STMA) of Trisakti conducted the activity of Pengabdian Kepada Masyarakat (PKM) by holding a digital insurance literacy and career preparation program for students. This activity aims to increase understanding of insurance (particularly digital insurance), promote insurance awareness, support the sustainable growth of the digital insurance industry, and provide students with information on how to prepare for work in digital insurance. Keywords: SNLIK 2025, Insurance Literacy, Insurance Inclusion, Insurtech, Digital Insurance.